Edukasi Ibu Tentang Pemberian Makanan Prelakteal Pada Bayi 0-6 Bulan Di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Tahun 2023 - Marta Armita Silaban; Damayanty S; Ika Damayanty; Angggun Lestari (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Early breastfeeding (ASI) in the first days of birth provides many benefits where there is colostrum which is proven to be very rich in antibodies which can increase the baby's immunity. Prelacteal food is given to babies in the first days after birth on the grounds that breast milk (ASI) has not been released so that the first days after birth are a vulnerable period for babies to receive prelacteal food/drinks. Prelacteal foods are dangerous because they can replace colostrum as the baby's earliest food. The impact of prelacteal feeding is that babies may get diarrhea, septicemia (bacterial infection in the blood), and meningitis, babies are more likely to suffer from intolerance to the protein in the formula, and develop allergies such as eczema. Method: this activity begins with the preparation of proposals and administration activities in May 2023. The implementation of this activity is educating mothers about prelacteal feeding to babies aged 0-6 months. Results: 30 participants in this activity were mothers who had babies aged 0-6 months in the village of Bangun Rejo. In its implementation, it was explained about the types of prelacteal feeding, the impact of prelacteal feeding, factors that can influence mothers to give prelacteal feeding. Conclusion: community service activities based on health education are carried out. This community service activity was carried out for 3 months starting in May-July 2023. The results of this community service regarding prelacteal feeding in infants aged 0-6 months.